KEDUDUKAN HAKIM PENGAWAS TERHADAP KURATOR DALAM PENGELOLAAN ASET PAILIT DI INDONESIA - Danial, Putri Sofiani (Ensiklopedia Education Review, 2025)
Abstract: This study aims to analyze the position and supervisory mechanism of the supervisory judge over the curator in the management of bankruptcy assets in Indonesia. Based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, the supervisory judge plays a crucial role in ensuring the accountability and integrity of the curator’s actions. However, in practice, such oversight has not been carried out optimally. This research employs a normative juridical approach with a descriptive-qualitative analysis method, using primary legal materials in the form of legislation and court decisions, as well as secondary legal sources from academic literature. The findings reveal that the supervisory judge faces various juridical, technical, and practical obstacles, including ambiguous legal norms, lack of digital infrastructure, and excessive judicial workload. Therefore, regulatory reform, digital integration of reporting systems, and technical capacity-building for supervisory judges are necessary to strengthen the oversight function. With these improvements, Indonesia’s bankruptcy system can operate more transparently, fairly, and efficiently.Keywords: supervisory judge, curator, bankruptcy assets, bankruptcy law, judicial oversight